Primum Non Nocere: is shared decision-making the answer?. Issue 1 (December 2016) - Santhirapala, Ramai; Moonesinghe, Ramani
Abstract Surgical ambition is rising, with the Royal College of Surgeons reporting an increase in the number of procedures by a million over the past decade (Royal College of Surgeons. Surgery and the NHS in Numbers. Available fromhttps://www.rcseng.ac.uk ). Underpinning, this is a rapidly growing population, especially those in the over 85 age group, coupled with rising perioperative expertise; options for surgery are now present where conditions were once managed conservatively. Matching the right patient to the right procedure has never been so pertinent (Bader, Am Soc Anesthesiol 78(6), 2014). At the heart of these increasingly complex decisions, which may prove fatal or result in serious morbidity, lies the aspiration of shared decision-making (SDM) (Glance et al., N Engl J Med 370:1379–81, 2014). Shared decision-making is a patient-centred approach taking into account the beliefs, preferences and views of the patient as an expert in what is right for them, supported by clinicians who are the experts in diagnostics and valid therapeutic options (Coulter and Collins, Making shared decision-making a reality: no decision about me, without me, 2011). It has been described as the pinnacle of patient-centred care (Barry et al., N Engl J Med 366:780–1, 2012). In this commentary, we explore further the concept of shared decision-making, supported by a recent article which highlights critical deficits in current perioperative practice (Ankuda et al., Patient Educ Couns 94(3):328–33, 2014). This article was chosen for the purposes of this commentary as it is a large study across several surgical specialties investigating preoperative shared decision-making, and to our knowledge, the only of this kind.